Competency model of sports coaches in multi-discipline coaching science - Masayu Rizka Risjanna; Novrizal Achmad Novan; Syifa F. Syihab; Dery Rimasa (Physical Education Departement of University PGRI Jombang, 2025)
To achieve high performance in sports requires integrated and continuous preparation between several factors in the training process that must be implemented to achieve an increase in the athlete's abilities. One factor in achieving maximum performance for an athlete is that the quality of the coach plays an important role in helping an athlete. The method used was an experiment by providing treatment to sports coaches in Manggar District. East Belitung, totaling 18 people as research subjects. Furthermore, the constituent variables include: physical training knowledge test, psychological knowledge test, injury management knowledge test and nutritional coverage test: practice of identifying daily food and drink consumption. Data analysis uses the ANOVA data regression model test to determine predictions by carrying out variance analysis and using factor analysis (Exploratory Factor Analysis) to analyze which variables have the dominant value in the trainer's competence.